O‐Acyl isopeptide method: development of an O‐acyl isodipeptide unit for Boc SPPS and its application to the synthesis of Aβ1‐42 isopeptide. (28th May 2014) - Yoshiya, Taku; Uemura, Tsuyoshi; Maruno, Takahiro; Kubo, Shigeru; Kiso, Yoshiaki; Sohma, Youhei; Kobayashi, Yuji; Yoshizawa‐Kumagaye, Kumiko; Nishiuchi, Yuji
<x xml:space="preserve">Abstract</x> The O‐acyl isopeptide method was developed for the efficient preparation of difficult sequence‐containing peptide. Furthermore, development of the O‐acyl isodipeptide unit for Fmoc chemistry simplified its synthetic procedure by solid‐phase peptide synthesis. Here, we report a novel isodipeptide unit for Boc chemistry, and the unit was successfully applied to the synthesis of amyloid β peptide. Combination of Boc chemistry and the isodipeptide unit would be an effective method for the synthesis of many difficult peptides. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.